Chronicle - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1998)
1. REPORT - 27-th Winter School on Molecular and Quantum Acoustics in Ustroń, Beskidy Mountains, organized by the Upper Silesian Division of the Polish Acoustical Society, located in Gliwice at the Institute of Physics, Silesian Technical University; 2. DISSERTATION - The Methods of Measurements and Analysis of the Acoustic Emission Signal, dissertation of Zbigniew Ranachowski, D.Sc was held on March, 6-th, 1998 at Cracow University of Mining and Metallergy. The publication of the dissertation in physical acoustics was supervised by Professor Ignacy Malecki. The habilitation is employed as a head of the laboratory in the Institute of Fundamental Technological Rasearch in Warsaw; 3. DISSERTATION - Perception of modulation of single components in harmonic multitone [in Polish] by Maurycy J. Kin, Institute of Telecommunications and Acoustics, Wrocław University of Technology, 29 April 1998, supervisor: Andrzej B. Dobrucki; 4. DISSERTATION - Analysis of acoustic emission signal of the temporomandibular joint for diagnostic purposes [in Polish] by Waldemar Lis, Department of Acoustics, Technical University of Gdańsk, 19 May 1998, supervisor: R. Salamon.